Lumped-parameter model of renal hemodynamics - Ng, David Chee Eng. (2008)
The blood flow through a porous and distensible vessel such as a glomerular capillary is studied using a lumped-parameter model, and based on simplified Navier-Stokes’ equations to derive the governing equations in the form of second-order hyperbolic partial differential equations in pressure. Further modelling of the autoregulation of flow is performed based on a extravascular tissue-pressure model. Lumped-parameter model of a compliant, porous vescular compartment was studied through simplification of Navier-Stokes equation where hyperbolic second-order partial differential equations governing flow and pressure were derived.